Somatostatin Receptors 2 and 5 Are the Major Somatostatin Receptors in Insulinomas: An in Vivo and in Vitro Study - Jérôme Bertherat; Florence Tenenbaum; Karine Perlemoine; Catherine Videau; Jean‐Louis Alberini; Byron C. Richard; B. Dousset; Xavier Bertagna; Jacques Epelbaum (2003)
Abstract Somatostatin (SRIF) receptors (sst) are present on normal pancreatic endocrine β-cells. However, the use of SRIF analogs in the scintigraphic imaging of insulinomas and in the medical management of these tumors seems to be restricted to a subgroup of patients. The aim of this study was to determine the prevalence of sst expression in vitro and characterize sst subtype binding in insulinomas and its correlation with in vivo sst receptor scintigraphy (SRS). In vitro studies were performed on 27 insulinomas from 25 patients: 22 with benign and three with malignant tumors. Semiquantitative RT-PCR of sst mRNAs was performed for 20 of these insulinomas. Sst2 and sst5 were expressed in 70%, sst1 in 50%, and sst3 and sst4 subtypes only in 15–20% of the tumors. 125I-Tyr0DTrp8SRIF14 binding was assessed by quantitative autoradiography in 18 insulinomas, and competition experiments were performed with SRIF14 and L797–591, L779–976, L796–778, L803–087, L817–818, selective agonists of the five sst subtypes, and BIM23244, a selective agonist of sst2 and sst5. Significant specific binding was observed in 72% of the insulinomas. Displacement experiments with ligands of higher affinity for each of the sst receptors revealed significant binding with the sst2 and sst5 ligands in 72%, sst3 in 44%, sst1 in 44%, and sst4 in 28% of cases. All insulinomas displaying sst2 binding were also sst5 sensitive. However, the ratio of sst5/sst2 displacement was variable and only equal to that for SRIF14 in experiments with the sst2/sst5 agonist BIM23244. SRS was performed 10 times in nine patients; it detected 60% of the tumors, including metastases of a malignant insulinoma. All the tumors detected by SRS displayed high levels of 125I-Tyr0DTrp8SRIF14 binding. The mechanisms underlying the loss of expression of sst2/sst5 in a third of insulinomas remains to be determined, but this loss of expression may be involved in β-cell dysfunction.